Nexus between Industry 4.0 and environmental sustainability: A Fourier panel bootstrap cointegration and causality analysis - Bildirici, Melike; Ersin, Ozgur Omer (ELSEVIER SCI LTD, 2023)
The paper aims at investigation of the nexus between Industry 4.0 (I4.0) and environmental sustainability in addition to exploring the long-run and short-run effects of Industry 4.0 on CO2 emissions. For this end, energy consumption, internet and communication technology (ICT) exports, research and development (R&D), artificial intelligence (AI), ICT technology patents and bitcoin are taken as control variables of Industry 4.0 for a panel of 9 countries that contribute to 62% of the total CO2 emissions in the world. For this purpose, the paper follows two approaches. First, the paper proposes utilization of AI and ICT technology patents, technology-related R&Ds and ICT exports as variables of I4.0 in addition to investigating the effects of economic growth, energy consumption and bitcoin. Second, to control structural changes and nonlinearity in the cointegrating relations and existence of degenerate cointegration, Fourier panel bootstrap autoregressive distributed lag model (FPBARDL) is utilized. Afterwards, FPBARDL based long, short and strong causality analyses are conducted. The empirical findings revealed positive impacts of all I4.0-related variables on emissions in the long-run. Though I4.0 related AI and ICT innovation has no direct effect in the short-run, its effects are determined through increased energy con-sumption towards emissions. The strong positive effects of energy consumption and positive effects of economic growth, ICT exports and R&D are observed both in the short and long-run. In addition to positive impacts of I4.0 on environment, the findings favor insufficiency of policies focusing on lowering emissions in I4.0 context.Policy recommendations include strong commitment to energy efficiency and renewable energies and trade policies with environmental concerns.
Keywords: Environmental sustainability; Industry 4; 0; Cointegration; Economic growth; International trade; Innovation; Panel causality; RENEWABLE ENERGY-CONSUMPTION; LAGRANGE MULTIPLIER TEST; ECONOMIC-GROWTH; CO2 EMISSIONS; MODEL; TECHNOLOGIES; PROACTIVITY; PERFORMANCE; INTEGRATION; IMPACT; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology